Evaluating the concept of three-dimensional printing guided endodontics in the dog - Peng, Jiahui; Yang, Jie; Liu, Ruiyu; Liu, Haifeng; Zhong, Zhijun; Peng, Guangneng; Zhang, Kun; Zheng, Chengli; Zhang, Ming; Zhou, Ziyao (Frontiers in Veterinary Science, 2024)
IntroductionGuided endodontics represents an effective method for achieving safe and reliable endodontic surgery in human medicine. However, it is rarely employed in small animal dentistry. This study employed finite element analysis and three-dimensional (3D) printing techniques to explore the feasibility of guided endodontics in Beagle mandibular teeth.MethodsThe methodology included the processing of Computed Tomography (CT) data, the creation of mathematical and 3D printing templates of the root canal pathways, and the evaluation of dog 3D printing guided endodontics compared with classic root canal method using radiograph.ResultsIn this experiment, the coordinates of the central point of pulp crown and apex point for each tooth were recorded. Based on the extension line of the central point of dental root canal orifice and the apex point, guided endodontic templates were designed on each root canal of 20 teeth in the Beagle mandible. Among them, the average relative deviation of guided endodontics and classic root canal method was 4.28%  ±  2.75%, and the mean angular deviation was 1.90  ±  0.25°.DiscussionOur research indicated that dog 3D printing guided endodontics has accurate position, direction, and length, which may assist veterinary dentistry in root canal treatment in small animals.